2015
DOI: 10.1200/jco.2014.58.6412
|View full text |Cite
|
Sign up to set email alerts
|

Refining American Joint Committee on Cancer/Union for International Cancer Control TNM Stage and Prognostic Groups for Human Papillomavirus–Related Oropharyngeal Carcinomas

Abstract: An RPA-based TNM stage grouping (stage I/II/III: T1-3N0-N2b/T1-3N2c/T4 or N3, with M1 as stage IV) is proposed for HPV-related OPC as a result of significantly improved survival prediction compared with the seventh edition TNM, and prognostication is further improved by an RPA-based prognostic grouping within the American Joint Committee on Cancer/Union for International Cancer Control TNM framework for HPV-related OPC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
305
1
9

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 356 publications
(353 citation statements)
references
References 25 publications
23
305
1
9
Order By: Relevance
“…Joo et al 25 reported a significant positive correlation between lymph node size and high-risk HPV status and a significant positive correlation between lymph node size and cystic nodal metastases, yet with an overall better diseasespecific survival rate in HPV-related head and neck squamous cell carcinoma compared with HPV-negative tumors. Huang et al 5 also found that N2a disease had better overall survival compared with N1 disease, applying traditional TNM staging in a cohort of patients with HPV-related OPSCC. The results of Joo et al 25 and Huang et al 5 support our hypothesis that solid or viable nodal metastatic burden may be prognostically more important, given the intranodal cystic changes frequently observed in HPV-related OPSCC.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Joo et al 25 reported a significant positive correlation between lymph node size and high-risk HPV status and a significant positive correlation between lymph node size and cystic nodal metastases, yet with an overall better diseasespecific survival rate in HPV-related head and neck squamous cell carcinoma compared with HPV-negative tumors. Huang et al 5 also found that N2a disease had better overall survival compared with N1 disease, applying traditional TNM staging in a cohort of patients with HPV-related OPSCC. The results of Joo et al 25 and Huang et al 5 support our hypothesis that solid or viable nodal metastatic burden may be prognostically more important, given the intranodal cystic changes frequently observed in HPV-related OPSCC.…”
Section: Discussionmentioning
confidence: 98%
“…Univariate Cox proportional hazard models were calculated to identify predictors of TF among the following variables: age (younger than 70 years versus 70 years and older), sex, T-stage, N-stage, primary tumor location (tonsil or tongue base), rECS, tobacco use (ever or never used tobacco products), calendar year of treatment, and solid-versus-cystic lymph nodes. 5 A multivariate Cox proportional hazard model was performed by using the same variables with a forward inclusion threshold of 0.1. We used Pearson statistics to identify the correlation among variables that were included in the final Cox model.…”
Section: Primary End Points and Statistical Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, next-generation sequencing (NGS), the evaluation of miRNA expression, proteomic and transcriptome profiling and the microbiome, have been explored in different tumors including HNSCC and sometimes OPSCC, TSCC and BOTSCC (37-39, 60-83). Finally, based on accumulated data, previous staging has been re-classified for HPV-positive OPSCC (84,85). Below, some of these attempts are described in more detail.…”
Section: Studies On οTher Markers and Re-staging Of Hpv-positive Tonsmentioning
confidence: 99%
“…Therefore, a new staging system was proposed, evaluating patients with p16 Ink4a positive and p16 Ink4a negative OPSCC separately (84). This staging system was later validated (85) and is now included in the eighth edition of the AJCC/UICC TNM staging system manual.…”
Section: Studies Disclosing Differences Between Hpvpositive and Hpv-nmentioning
confidence: 99%